Aspiration, equality, and privilege in education: Exploring an alternative education model for the Malays - Mohd Kamalludeen, Rosemaliza; Ismail, Nik Ahmad Hisham; Idrus, Faizah (The International Institute of Knowledge Management (TIIKM), 2016)
All efforts done by the Malaysian government in ensuring elevated education quality would always have relevance with the progress of the Malay society and their status quo in the Malaysian constitution. Ironically, the Malay society has always been perceived as underachievers educationally and economically when compared to other races living in Malaysia. Therefore, concerns over the suitability of an education system that is deemed fit for the Malays in order for them to progress in the globalized arena has been in constant debate. Would the Malay privilege stipulated by the Malaysian Constitution still be relevant and significant in producing a Malay society that is equally competitive educationally and economically with other fellow Malaysians of different races? What would an ideal education system for the Malays include? Would the reforms recommended in the new Malaysian Education Blueprint 2015-2025 be suitable for the Malay society to compete globally? This qualitative study explored the demands of the Malay ethnic society in terms of an “ideal” education system that would allow the Malays to be globally competitive. A series of semi-structured interviews were conducted with the Malay people of different socio-economic status including politicians, blue collar workers, and corporate executives to determine an ideal education model deemed fit to ensure economic and political progress of the Malay society in Malaysia. The study found key areas that build up the ideal Malay education model, including an apolitical education system supported by substantial government funding and emphasis on the rural area development.